Challenges of Differential Diagnosis, Symptoms of Coronavirus Disease 2019 (COVID-19) or Cannabinoid Hyperemesis Syndrome (CHS)? A Rare Case Report - Bijan PIRNIA; Kambiz PIRNIA; Parastoo MALEKANMEHR; Alireza ZAHIRODDIN (Tehran University of Medical Sciences, 2020)
Coronavirus Disease 2019 (COVID-19) has become a pandemic since Mar 2020. Iran has been one of the first countries dealing with the outbreak of COVID-19 and severe measures have been adopted to limit viral transmission. Cannabinoid hyperemesis syndrome (CHS) is a syndrome of cyclic vomiting associated with cannabis use. Many of the clinical symptoms of COVID-19 are similar to CHS. Here, we report a 26-year-old man with CHS, that the presented symptoms are similar to COVID-19 in many cases, and in our knowledge, it is the first in this type. Paying attention to the symptoms can help to differential diagnosis of the two diseases and reduce the burden of treatment during this critical period.